The Repeated Evolution of Behavior - York, Ryan A.; Fernald, Russell D. (Frontiers in Ecology and Evolution, 2017)
A major tool in the evolutionary biologist’s kit is to study the repeated emergence of certain biological traits. Employment of this tool has allowed substantial recent advances to be made in understanding the adaptive molecular basis of certain key biological traits. However behavior, one life’s most pervasive and complex traits, is not one. Here we review the concepts of repeated evolution and how they apply to behavior. We assess the distribution and evolutionary dynamics of known cases of repeated behavioral evolution and examine their prospects for success in identifying the genetic and mechanistic bases of behavior. We propose that studying adaptive radiations, such as that seen amongst the cichlids of Lake Malawi, will likely yield results quickly due to the tractability of genetic and comparative analyses. Finally we suggest some possible scenarios that might be observed in the pursuit of the adaptive molecular basis of behavior and advocate for research on a diverse number of case studies of behavioral evolution, allowing for a knowledge base from which general principles of behavioral evolution might be gleaned.